Comparison of the Clinical Efficacy of Boston Keratoprosthesis Type I and Repetitive Penetrating Keratoplasty for Refractory Keratopathy. Issue 2 (March 2020) - Chen, Yingxin; Wang, Cuiyu; Liu, Qiming; Wang, Ziyue; Gao, Minghong
Abstract : Objective: To compare the clinical efficacy of Boston Keratoprosthesis type I (B-KProI) and penetrating keratoplasty (PKP) for patients with refractory keratopathy after 1failed PKP in China. Method: The 42 consecutive cases with refractory keratopathy after 1 failed PKP, from July 2010 to December 2014, were divided into 2 groups according to the surgical method: KPro group (n = 21) and PKP group (n = 21). Visual acuity (LogMAR), corneal graft transparency, postoperative complications and corneal graft survival rate were observed. The follow-up time was 2 years. The Kaplan-Meier curve was used to analyze the survival rate of the two groups of corneal grafts. Results: The average best corrected visual acuity (BCVA) at 1, 6, 12, 18, and 24 months in KPro group were significantly lower than PKP group ( P  < 0.01). The best postoperative visual acuity and BCVA at postoperative 2 years in KPro group were lower than PKP group. The success rate of KPro group (86%) were significantly higher than PKP group (43%) ( P  < 0.01). There were no significant differences in indicate of complications in 2 groups including secondary glaucoma, secondary infectious corneal ulcer, corneal graft melting and endophthalmitis ( P  > 0.05). Conclusion: Compared with repetitive PKP, B-KProI had a higher success rate, improved postoperative visual acuity, reduced postoperative corneal transplant rejection rates and improved corneal graft survival rate. Abstract : Supplemental Digital Content is available in the text